Collegial spaces: experiences of a long-term women's graduate student friendship group - Nordyke, Dana R. (Kansas State University, 2022)
Women master’s students face a variety of unique challenges throughout their education including feeling like imposters or like they needed to justify why they were choosing their education over other life priorities (Lininger et al., 2016; Younes, 1998). While Gordon (2016) identified barriers to graduate student success in master’s level programs including being “disconnected from peers” (p. 85), few studies have explored the experiences of women with close peer relationships formed during master’s programs. Additionally, the transitions literature includes a great foundation in transitioning into a master’s program e.g. Lopez (2013) and Perez (2016) but appears to be lacking in transitions that continue to occur during and after master’s degree programs, especially among women. The purpose of this qualitative case study was to explore how five women who attended graduate school together made meaning of their experiences while participating in an all-women friendship group both during and after the master’s program. The participants were selected using purposeful sampling. The participants were known, because the researcher, while not a participant in this study, was also a member of the same friendship group. The participant experiences and design of the study were viewed using symbolic interactionism as the theoretical framework. This study investigated how the participants described their experiences in the friendship group and the meaning of the friendships. The data collection included individual interviews, a group photo-elicited interview, and document analysis allowing the data to be triangulated. Throughout the data collection and analysis, the meaning of the friendships to the participants was sought through “such things as sensations, feelings, ideas, memories, motives, and attitudes” (Blumer, 1969, p. 4). The meaning each participant made of the friendships within the friendship group was derived from the social interactions they had with one another (and/or with others). The findings of this study suggest that women who were included in a friendship group with other women during their master’s program felt connected, were engaged in and out of the classroom, and felt supported in strengthening their mind, body, and spirit. In addition, the friendship group served to help them determine who they were both personally and professionally. Following the master’s program, involvement in a friendship group included navigating unforeseen challenges together and feeling strongly connected to other women who served as resources when encountering similar life challenges. A collegial space was created among women in the friendship group wherein they felt safe to gather and be themselves.
Keywords: Friendship group; Master's student; Women; Informal cohort; Transition; Collegial spaces